Strain engineering and process optimization for enhancing the production of a thermostable steryl glucosidase in Escherichia coli - Eberhardt, Maria Florencia (2017)
Biodiesels produced from transesterification of vegetable oils have a major problem in quality due to the presence of precipitates, which are mostly composed of steryl glucosides (SGs). We have recently described an enzymatic method for the efficient removal of SGs from biodiesel, based on the activity of a thermostable β-glycosidase from Thermococcus litoralis. In the present work, we describe the development of an Escherichia coli-based expression system and a high cell density fermentation process. Strain and process engineering include the assessment of different promoters to drive the expression of a codon-optimized gene, the co-expression of molecular chaperones and the development of a high cell density fermentation process. A 200-fold increase in the production titers was achieved, which directly impacts on the costs of the industrial process for treating biodiesel.